Measurements of THz and X-ray generation during metal foil ablation by TW, sub-relativistic laser pulses. (November 2020) - Nazarov, M M; Shcheglov, P A; Chaschin, M V; Garmatina, A A; Mitrofanov, A V; Sidorov-Biryukov, D A; Bernier, M; Muller, B; Panchenko, V Ya
Abstract: We discovered that intensity of ∼10 16 W/cm 2 and 20 mJ energy in femtosecond laser pulse is enough to observe THz emission from the rear side of metal foil in a vacuum. In the same experiment for 2-10 mbar air pressure and two-color pump similar energy of THz pulse form gas plasma was detected. Comparable amplitude and spectra of THz emission are also observed in reflection from the metal foil front side. X-ray emission is also studied as a criterion of intensity optimization. For much lower (10 14 W/cm 2 ) intensity reflected THz emission was detected as a result of optical rectification in a thin metal film with 10 −6 efficiency. While for sub-relativistic intensities the observed efficiency 10 −5 of THz generation from metal is higher than predicted by known theories. The main benefit of THz generation in metal is the absence of yield saturation at TW level of laser energy and above.